Somatotypes and anthropometric profile of elite Serbian Greco-Roman wrestlers - Casals, C.; Lopez-Gullon, J. M.; Trivic, T.; Drid, P. (International scientific and professional conference on wrestling: "Applicable research in wrestling", 2017)
The aim of this study was to compare the anthropometric profile of elite Greco-Roman wrestlers by their body mass. Somatotypes of 32 Serbian wrestlers were determined according to the Heath-Carter method, being balanced-mesomorphic in lighter athletes and mesomorph-endomorphic in heavier ones; statistically significant for endomorphy (r = -0.70, p < 0.001), mesomorphy ( r= -0.68, p < 0.001), and ectomorphy (r = 0.79, p < 0.001). Body fat percentage was calculated as: ( 6skinfolds*0.1051)+2.58, including triceps, subscapular, supraspinal, abdomen, thigh, and medial calf skinfolds; showing similar percentages in light and middle-weight categories, while heavier athletes presented higher body fat percentages (r = 0.73, p < 0.001). Therefore, weight-specific characteristics in body composition was reported in elite Greco-Roman wrestlers.